Development of a Chemistry Learning E-Module Based on Problem Based Learning on Reaction Rate Material to Improve Student Learning Outcomes - Sulfaidah Sulfaidah; Zulkarnaen Zulkarnaen; Mukhamad Nurhadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2026)
This study aims to develop a valid, practical, and effective Problem Based Learning (PBL) based chemistry e-module on reaction rate material for grade XI students at MA DDI Bontang in improving learning outcomes. This study uses the Research and Development (R&D) method with the ADDIE model which includes the Analyze, Design, Develop, Implement, and Evaluate stages. The resulting product is a PBL-based e-module as a more interesting and non-monotonous teaching material. Data collection techniques were carried out through observation, questionnaires, pretests, and posttests. The results showed that the developed e-module was very feasible to use based on validation by material experts of 90.0% and media experts of 87.0%. The use of PBL-based e-modules was also proven to be effective in improving student learning outcomes. The average posttest score of 85.4 was higher than the pretest score of 52.0. The t-test results showed that the t-count value of 19.146 was greater than the t-table of 2.042 at a significance level of 0.05, so there was a significant effect of the use of e-modules on student learning outcomes. In addition, student responses to the e-module were positive at 84.8%. Thus, the PBL-based e-module is feasible and effective for use in chemistry learning on reaction rates